2023
DOI: 10.1111/wej.12868
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of UV‐Cl and UV‐H2O2 advanced oxidation processes in the degradation of contaminants from water and wastewater: A review

Abstract: Applications of advanced oxidation processes (AOPs) in water and wastewater treatment have been the subject of growing interest throughout the last decade. Although UV/hydrogen peroxide (UV‐H2O2) is the most established technology among the UV‐AOPs, UV‐chlorine (UV‐Cl) is emerging as a reliable and potentially more cost‐effective alternative. Recent studies have indicated that UV‐Cl processes may be more efficient and economically favourable for the degradation of some chemicals of emerging concern from contam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…In a UV/peroxide process, the removal of COD and BOD occurs through a combination of oxidation and biodegradation processes. The hydroxyl radicals produced by the UV/peroxide reaction attack and oxidize the organic pollutants, breaking them down into simpler, biodegradable compounds [37], yielding an effluent that microorganisms can potentially use as the pollutant load has decreased to a level where biodegradation processes can occur, further reducing the pollutant load [38]. Table 9 shows the removal percentages achieved in this research compared to other AOPs used for tannery water treatment.…”
Section: Optimization and Validation Of Uv/h 2 O 2 Operating Conditionsmentioning
confidence: 96%
See 1 more Smart Citation
“…In a UV/peroxide process, the removal of COD and BOD occurs through a combination of oxidation and biodegradation processes. The hydroxyl radicals produced by the UV/peroxide reaction attack and oxidize the organic pollutants, breaking them down into simpler, biodegradable compounds [37], yielding an effluent that microorganisms can potentially use as the pollutant load has decreased to a level where biodegradation processes can occur, further reducing the pollutant load [38]. Table 9 shows the removal percentages achieved in this research compared to other AOPs used for tannery water treatment.…”
Section: Optimization and Validation Of Uv/h 2 O 2 Operating Conditionsmentioning
confidence: 96%
“…In this study, COD and color removal results were relatively lower than those of Saranya et al [39], while removal rates for Cr, N-NH3, and TSS were lower than those attained in this study; [40] applied a UV//H2O2 process in the fluxes of a tannery and found COD removals of 18.8%, BOD 30.2%, TSS 49%, Cr 65.7%, and chlorides 43%, which were lower than those reported in this study; nevertheless, color removal was greater compared to that achieved in this research; [41] reported the implementation of two AOPs (UV/H2O2 and TiO2/H2O2/UV) in which they evaluated the removal of COD, color, and N-NH3 showing removals of 18.8%, 67.36%, and 78.8%, respectively, for the UV/H2O2 process and 68.3% for COD, 91.5% for color and 90.7% for N-NH3 in the TiO2//H2O2/UV system, it can be seen that comparing the results with this study, the UV//H2O2 process obtained lower efficiencies while the TiO2 mediated system obtained removals above the system In a UV/peroxide process, the removal of COD and BOD occurs through a combination of oxidation and biodegradation processes. The hydroxyl radicals produced by the UV/peroxide reaction attack and oxidize the organic pollutants, breaking them down into simpler, biodegradable compounds [37], yielding an effluent that microorganisms can potentially use as the pollutant load has decreased to a level where biodegradation processes can occur, further reducing the pollutant load [38]. Table 9 shows the removal percentages achieved in this research compared to other AOPs used for tannery water treatment.…”
Section: Optimization and Validation Of Uv/h 2 O 2 Operating Conditionsmentioning
confidence: 96%